(untitled) (Comprehensive Journal of Science, 2026)
​This study aimed to determine the role of quality cost management in improving the quality of banking services at Jumhouria Bank, Al-Hadaeq Branch, Benghazi. The research adopted a descriptive-analytical approach, utilizing a comprehensive census method for the study population consisting of 30 employees and officials. Primary data were collected through a 24-item questionnaire distributed across six main axes. Statistical analysis was conducted using Cronbach’s Alpha for reliability, the correlation matrix, and simple linear regression. The results revealed a strong positive relationship between prevention and appraisal costs and service quality. The quality cost model explains 61.6% of the changes in service quality levels, while showing a clear inverse (negative) effect for both internal and external failure costs. Consequently, the study recommended adopting a specialized accounting system to classify quality costs, increasing proactive spending on training and prevention, and strengthening internal control mechanisms to reduce failure costs and customer complaints.